Importance of male partner's involvement in prevention of mother to child transmission of HIV/AIDS in Ethiopia: a systematic review and meta analysis until June 2021 - Shimeles Biru Zewude; Asrat Hailu Dagne; Tewodros Magegnet Ajebe (BMC, 2022)
Abstract Background To promote the prevention of mother-to-child transmission (PMTCT) of HIV/AIDS male partners play a significant role, especially in developing country were men's are a decision maker in domestic activity. When men are involved in PMTCT it would boost the service utilization and uptake of ART drugs. Thus this systematic review and Meta analysis aims to assess importance of male partner involvement in prevention of mother to child transmission of HIV/AIDS in Ethiopia. Methods Studies were accessed through an electronic web-based search mechanism from PubMed, Advanced Google Scholar, WHO databases and journals (African Health Monitor, Pan African Journal of Public Health), using independent and combinations of key terms together with a reference list of included studies. Two reviewers independently screened and assessed the quality of studies based on pre-specified criteria. When a disagreement between the two reviewers happened; the third reviewer was invited and resolve it based on the stated objectives and inclusion criteria. Measures of effects were pooled and random effect meta analysis was conducted. Results Ten studies met the inclusion criteria. The pooled prevalence of male involvement in PMTCT was 31.8% (95% CI; 22.3-41.3 I2 = 98.4%, p = 0.00). being urban residence(AOR = 2.43 95%CI;1.42-4.18), partner knowledge (AOR = 2.84 95%CI;1.90-4.22), knowledge on Antenatal care(AOR = 3.5 95%CI;1.80-6.76), partners who had no negative perception towards for PMTCT (AOR = 3.21 95%CI;2.18-4.72), government employee(AOR = 2.57 95%CI;1.76-3.75), partners informed of need to go for PMTCT(AOR = 3.83 95%CI;1.88-7.79), health institution related barriers(AOR = 2.6 95%CI;1.882-3.622), primary (AOR = 2.21 95%CI;1.29-3.80), and secondary education(AOR = 2.67 95%CI;1.69-4.19) were significant factors related with male partner involvement in prevention of mother to child transmission of HIV/AIDS. Conclusion The proportion of male involvement in the Prevention of mother-to-child transmission of HIV in Ethiopia was low. Interventions aimed at improving male participation in the Prevention of mother-to-child transmission should consider the factors related to it. Healthcare services may need to be inclusive and could help men active engagement in PMTCT programs.